Time to recovery of neonatal sepsis and its predictors in public hospitals of North Shoa Zone, Central Ethiopia - Befekadu Tesfaye Oyato; Teshome Ketema Sime; Tirunesh Debele; Husen Zakir Abasimel; Fikadu Tolesa Alemu; Samuel Boja Asfaw; Wuletaw Tadesse Mekonnin; Hana Israel Gesisa; Elleni Tesfaye Kebede (BMC Infectious Diseases)
Abstract Background Neonatal sepsis remains one of the most common causes of morbidity and mortality among neonates in developing countries. It can cause severe morbidities and sequelae, even though patients survive. Prolonged recovery time of neonatal sepsis leads to hospitalization, increased cost of treatments, antimicrobial resistance, disseminated intravascular coagulation, respiratory failure, septic shock, brain lesions, renal failure, and cardiovascular dysfunction, and eventually death. Thus, this study aimed to identify the time-to-recovery of neonatal sepsis and its predictors among newborns admitted to public hospitals in the North Shoa Zone, Central Ethiopia. Methods A retrospective cohort study was conducted among 508 septic neonates admitted to selected public hospitals in the North Shoa Zone between March 1, 2021, and March 1, 2023. A systematic random sampling method was used to select eligible medical records. The data were collected through the open data kit (ODK) Collect Android app and consequently exported to STATA version 17 for analysis. The data were analyzed using both univariable and multivariable Cox regression models. The adjusted hazard ratio (AHR) with its corresponding 95% confidence interval (CI) was employed. Results Of all septic neonates, 441 were recovered. The predictors of time-to-recovery of neonatal sepsis were premature rupture of membrane (PROM) (AHR = 0.37; 95% CI: 0.21, 0.63), intrapartum fever (AHR = 0.49; 95% CI: 0.32, 0.75), chest-indrawing (AHR = 0.50; 95% CI: 0.36, 0.68), fifth-minute appearance, pulse, grimace, activity, and respiration (Apgar) score less than seven (AHR = 0.54; 95% CI: 0.38, 0.77), gestational age between 37 and 42 weeks (AHR = 1.35; 95% CI: 1.06, 1.70), septic shock (AHR = 0.52; 95% CI: 0.31, 0.85). Conclusion The median time to recovery from neonatal sepsis in this study was comparable to the previous studies. Premature rupture of membranes, intrapartum fever, term gestational age, low fifth minute Apgar score, chest indrawing, and septic shock were the predictors of time-to recovery of neonatal sepsis. Therefore, birth attendants are advised to closely adhere to the obstetrics management protocols when providing care for women who have intrapartum fever and premature rupture of membranes, as this will help to minimize neonatal sepsis and the subsequent delay in recovery.